2009
DOI: 10.1111/igc.0b013e318197f847
|View full text |Cite
|
Sign up to set email alerts
|

Class II Radical Hysterectomy in Low-Risk IB Squamous Cell Carcinoma of Cervix: A Safe and Effective Option

Abstract: In treating a subset of patients with tumor size no greater than 2 cm and grade 1 to 2 squamous cell cancer, class II and class III radical hysterectomy are equally effective, but the former has far less complications than the latter.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
19
0
1

Year Published

2010
2010
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(21 citation statements)
references
References 20 publications
(12 reference statements)
1
19
0
1
Order By: Relevance
“…A study performed by Cai et al (15) also favoured class II RAH rather than class III in grade I and II cervical SCCs smaller than 2 cm. The authors reported similar oncological outcomes in the class II group, with significantly lower operating time, post-operative length of hospital stay, and estimated blood loss (15). It is worth noting that these two studies did not include stage IB2 cases.…”
Section: Discussionmentioning
confidence: 78%
“…A study performed by Cai et al (15) also favoured class II RAH rather than class III in grade I and II cervical SCCs smaller than 2 cm. The authors reported similar oncological outcomes in the class II group, with significantly lower operating time, post-operative length of hospital stay, and estimated blood loss (15). It is worth noting that these two studies did not include stage IB2 cases.…”
Section: Discussionmentioning
confidence: 78%
“…Patients with low risk early stage disease undergoing radical surgical treatment have a survival of nearly 100%. [19] However patient with more advanced disease have lower reported outcome.…”
Section: Survivalmentioning
confidence: 99%
“…Patients with low-risk early-stage disease, undergoing radical surgical treatment have a survival of nearly 100% [20]. However, patients with more advanced disease have lower reported outcomes.…”
Section: Survivalmentioning
confidence: 99%